Persian adaptation and validation of the user version of The Mobile Application Rating Scale (uMARS) - Zeinab Kohzadi; Shahabedin Rahmatizadeh; Zahra Kohzadi; Saeideh Valizadeh-Haghi (PLoS ONE, 2025)
Objective Health applications (apps) enable patients to make decisions regarding their health utilizing digitally-enabled processes for care, expand accessibility to healthcare service delivery, and raise public awareness of health. In many languages, there is still a lack of an instrument that assesses how patients perceive apps. This study aims to adapt and validate the User Version of the Mobile Application Rating Scale (uMARS) in Persian and evaluate the overall quality of the Persian meditation apps. Methods This cross-sectional study population comprises 86 healthcare workers in a health center in the west of Iran. The sample size was determined using Cochran’s formula. First, the uMARS was translated into Persian. Then, validity was assessed using the Content Validity Ratio (CVR), Content Validity Index (CVI), and face validity. Cronbach’s alpha and Intraclass Correlation Coefficients (ICC) were used to assess reliability. Among the 124 meditation apps, Aramia met the criteria included in the study and was selected to evaluate objective quality, subjective quality, and perceived impact. Results The majority of the participants were female (82.55%). More than half of the participants had a bachelor’s degree (58.14%). The CVR, CVI, ICC, and Cronbach’s alpha values were obtained as 0.79. 0.90, 0.93, and 0.86, respectively. These Findings revealed that the Persian version of the questionnaire has sufficient reliability and validity. Among the three subscales, perceived impact received the highest mean score (3.96 ± 0.37), and a total score of 3.74 ± 1.04 was obtained. Conclusions A Persian version of uMARS is a valid and reliable tool for evaluating the quality of mobile health apps from the user’s point of view during the development and testing process and improving the app’s quality.